2021
DOI: 10.1021/jacs.1c04815
|View full text |Cite
|
Sign up to set email alerts
|

Alkali Metal Adducts of an Iron(0) Complex and Their Synergistic FLP-Type Activation of Aliphatic C–X Bonds

Abstract: We report the formation and full characterization of weak adducts between Li+ and Na+ cations and a neutral iron(0) complex, [Fe­(CO)3(PMe3)2] (1), supported by weakly coordinating [BArF 20] anions, [1·M]­[BArF 20] (M = Li, Na). The adducts are found to synergistically activate aliphatic C–X bonds (X = F, Cl, Br, I, OMs, OTf), leading to the formation of iron­(II) organyl compounds of the type [FeR­(CO)3(PMe3)2]­[BArF 20], of which several were isolated and fully characterized. Stoichiometric reactions with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 71 publications
1
9
0
Order By: Relevance
“…[3][4][5][6][7][8][9][10] This is a consequence of the synthetic difficulty in accessing discrete intermediates who both retain reactivity towards the substrate of interest and the requisite stability for adequate characterization. [4][5][6][7][8] This complexity also can be manifested in measuring essential kinetic data for these processes, which is often a requirement to gain insight into the controlling events that can influence catalysis. [9,10] In this context, we have recently reported the use of a series of electroanalytical methods to analyze several ligated Co(I) complexes in the activation of a wide range of benzylic halides.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[3][4][5][6][7][8][9][10] This is a consequence of the synthetic difficulty in accessing discrete intermediates who both retain reactivity towards the substrate of interest and the requisite stability for adequate characterization. [4][5][6][7][8] This complexity also can be manifested in measuring essential kinetic data for these processes, which is often a requirement to gain insight into the controlling events that can influence catalysis. [9,10] In this context, we have recently reported the use of a series of electroanalytical methods to analyze several ligated Co(I) complexes in the activation of a wide range of benzylic halides.…”
Section: Introductionmentioning
confidence: 99%
“…[2] Although significant progress has been reported, experimental mechanistic studies remain a challenge. [3][4][5][6][7][8][9][10] This is a consequence of the synthetic difficulty in accessing discrete intermediates who both retain reactivity towards the substrate of interest and the requisite stability for adequate characterization. [4][5][6][7][8] This complexity also can be manifested in measuring essential kinetic data for these processes, which is often a requirement to gain insight into the controlling events that can influence catalysis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The base additive may not only aid in increasing the reaction temperature of the mixture and shift the reaction equilibrium , but also, more importantly, direct the reaction to go through the energetically more favorable transition states. Similar observations in both heterogeneous and homogeneous reactions have also been reported, wherein the role of the alkali metal cation as a Lewis acid cocatalyst is established. , The production of H 2 increased with an increasing amount of KOH (entries 8, 4, and 9), but a further increase of the base actually led to a reduction of the activity (entries 10 and 11), possibly due to an expedited catalyst decomposition in a strongly basic reaction mixture. Control experiments were conducted using a mixture of CH 3 CHO/H 2 O and CH 3 CH 2 OH/H 2 O (10 mL, v/v 8:2) in the presence of 10 M KOH but without the use of any catalyst.…”
Section: Resultsmentioning
confidence: 99%
“…43 Another recent compelling example of productive interaction of iron complexes with simple alkali salts was reported by Young. 44 It was demonstrated that Fe 0 (PMe 3 ) 2 (CO) 3 reacted with [M I ] + [BAr F 20 ] − salts to yield weakly bound adducts [Fe 0 (PMe 3 ) 2 (CO) 3 •M] + [BAr F 20 ] − (M = Li, Na). The latter was proved to activate organic halides R′-X in a synergistic pathway much reminiscent of frustrated-Lewis-pair-like activation processes (Scheme 5e).…”
Section: Dalton Transactionsmentioning
confidence: 99%